Rheumatological complications associated with the use of indinavir and other protease inhibitors. Issue 1 (1st January 2002) - Florence, E; Schrooten, W; Verdonck, K; Dreezen, C; Colebunders, R
Abstract : Several cases are reported of rheumatological pathology (temporomandibular dysfunction, frozen shoulder, Dupuytren's disease, and tendinitis) most probably related to the intake of indinavir in HIV positive patients. A survey using an anonymous questionnaire of 878 people with HIV infection treated with antiretroviral drugs suggests that other protease inhibitors may also cause arthralgia.